Role of Management Accounting Practices in Determining Customer Satisfaction in Nepalese Commercial Banks - Mahataman, Tribhuvan Kumar (THE ACADEMIA, 2025)
Management accounting techniques that improve customers satisfaction in banks include decision making, costing, performance evaluation, time driven activity-based costing and budgeting. The study focuses on present practices of management accounting for customer satisfaction in Nepalese commercial bank. Management accounting practices (MAPs) play important role in customer satisfaction through enhancing Nepalese commercial banks’ decision-making, financial efficiency, and service quality. This study examines how MAPs and customer satisfaction are related, with a particular emphasis on decision-support systems, cost control, performance evaluation, benchmarking, TDABC and budgeting in commercial banks. The study used a survey method to conduct a quantitative investigation and a descriptive research design to examine the management accounting practices and customer satisfaction of Nepalese commercial banks. Based on judgmental sampling 300 branch managers out of 591 branch managers and 350 customers provided questionnaire for this study. Using cluster sampling, the five banks are chosen based on their largest paid-up capital. In order to fulfill the research objectives, primary data are collected using online questionnaires as well as printed questionnaires. On the basis of responses given by 285 branch managers out of which 300 usable data and 285 responses received from customers out of which 350 are usable data, data are analyzed using various statistical tools. The analysis showed that commercial banks are practicing management accounting for customer satisfaction. The result of the study indicated that there is positive association between management accounting practices and customer satisfaction in Nepalese Commercial Banks. The study concludes that Nepalese commercial banks should adopt robust management accounting practices to enhance their customer satisfaction.